Effects of anthropogenic activities on nutrient parameters in the North Eastern Mediterranean Sea (Bay of Sığacık/Aegean Sea) - Çulha Saniye Türk; Karaduman Fatma Rabia; Gündoğdu Ayşe; Barış Kamil Emre (Oceanological and Hydrobiological Studies)
This study aims to examine the physicochemical parameters of seawater (temperature, pH, salinity, dissolved oxygen, suspended particulate matter, ammonium-nitrogen, nitrite-nitrogen, nitrate-nitrogen, and phosphate-phosphorus, burnable organic matter in the sediment), and possible effects of pollution in Sığacık Bay where different anthropogenic activities are carried out. Samples of surface seawater (0 m), bottom seawater (2 m), and sediment were collected monthly from four sampling sites between September 2013 and September 2014. Annual mean nutrient values were determined as 1.6 ± 0.14 μg.at.NH4+-N l-1, 0.1 ± 0.01 μg.at.NO2--N l-1, 0.8 ± 0.08 μg.at.NO3--N l-1, 0.7 ± 0.08 μg.at.PO43--P l-1, SPM 21.4 ± 0.33 mg l-1. The BOM content in the sediment was 5.6 ± 0.39%. As a result of the study, it was determined that Sığacık Bay was polluted by anthropogenic point and non-point source pollution. According to the water quality criteria, the bay was found to be in the group of polluted seawater in terms of phosphate phosphorus.